Correct Modeling of Cisplatin: a Paradigmatic Case - Tasinato, Nicola (Angew Chem Int Ed Engl, 2017)
Quantum chemistry is a useful tool in modern approaches to drug and material design, but only when the adopted model reflects a correct physical picture. Paradigmatic is the case of cis‐diaminodichloroplatinum(II), cis‐[Pt(NH(3))(2)Cl(2)], for which the correct simulation of the structural and vibrational properties measured experimentally still remains an open question. By using this molecule as a proof of concept, it is shown that state‐of‐the‐art quantum chemical calculations and a simple model, capturing the basic physical flavors, a cis‐[Pt(NH(3))(2)Cl(2)] dimer, can provide the accuracy required for interpretative purposes. The present outcomes have fundamental implications for benchmark studies aiming at assessing the accuracy of a given computational protocol.